Migration and Labor Market Integration in Europe - David Dorn; Josef Zweimüller (Institute of Labor Economics (IZA), 2021)
The European labor market allows for the border-free mobility of workers across 31 countries that cover most of the continent's population. However, rates of migration across European countries remain considerably lower than interstate migration in the United States, and spatial variation in terms of unemployment or income levels is larger. We document patterns of migration in Europe, which include a sizable migration from east to west in the last twenty years. An analysis of worker-level microdata provides some evidence for an international convergence in wage rates, and for modest static gains from migration. We conclude by discussing obstacles to migration that reduce the potential for further labor market integration in Europe.
Keywords: F22; F53; J31; J61; 330; labor migration; wages; Europe; European Union single market